"Remembering Semitism" or "On the Prospect of Re-Membering the Semites". (1st April 2016) - ,
Abstract : Today, a growing number of French Jews embrace the far-right French Front National party, which has a long history of anti-Semitism – how did we get here? How is it that Jews turn to the French authorities for protection against so-called Muslim anti-Semitic violence? How is it that we see a similar pattern across Europe: in Belgium, The Netherlands, Denmark, and Britain? This essay addresses these questions by calling attention to the role played by the absent-present Christian West in creating and aggravating tensions between Jews and Muslims while seemingly fulfilling the role of mediation between the two. The essay suggests that current popular images of Jews and Muslims circulating in Western media ironically echo nineteenth-century European depictions of Semites – both Jews and Muslims as devoted monotheistic fanatics controlled by zeal and despotism and in need of external salvation. The bulk of the essay thus focuses on "Semitism" and examines the role of nineteenth-century European philology in disseminating Western perceptions of Jewish and Muslim inferiority. Finally, the essay advocates a re-appropriation of Semitism as an alternative memory, or rather a re-memory which as such is also a re-membering of Jews and Muslims along their shared historical position as radical Others within the hegemonic, Western, Euro-Christian epistemological order.